1997
DOI: 10.2169/internalmedicine.36.851
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Aspiration Pneumonia.

Abstract: Aspiration pneumonia is associated with decreases in both swallowing and cough reflexes and is the most common cause of death in the elderly. Basal ganglia strokes might predispose these patients to develop pneumonia owing to reductions of both reflexes, resulting in frequent aspiration during sleep. An impairment of dopamine metabolism in the basal ganglia is observed in these patients and levodopa administration improves the impaired swallowing reflex. Both swallowing and cough reflexes are mediated by endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Therefore, it is suggested that the bedridden condition encourages infection or accumulation of C. albicans, Pseudomonas spp., and S. marcescens in plaque and, thus, is a risk factor for respiratory tract infection by aspiration. Bedridden subjects were also found to be subject to a progressive loss of protective reflexes, which is also a factor with aspiration pneumonia in the elderly [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that the bedridden condition encourages infection or accumulation of C. albicans, Pseudomonas spp., and S. marcescens in plaque and, thus, is a risk factor for respiratory tract infection by aspiration. Bedridden subjects were also found to be subject to a progressive loss of protective reflexes, which is also a factor with aspiration pneumonia in the elderly [25].…”
Section: Discussionmentioning
confidence: 99%
“…This possibility can present in adults because the fetal protective reflex of glottic closure is not eliminated after birth but continues during adulthood and is important for coughing when there is exhalation against a partially closed glottis in order to clear secretions and materials from the lower airways. A closed glottis participates in the Valsalva maneuver [95].…”
Section: Discussionmentioning
confidence: 99%
“…As for regulation of the swallowing reflex, which is mediated by endogenous substance P released from vagal sensory nerves in the pharynx and upper airway, substance P plays an important role as a regulator. 31) Some ingredients of Hange-koboku-to might be involved in the changes in substance P. Magnorol and konokiol from Magnoliae Cortex, and perillaldehyde from Perillae Herba have been found to have inhibitory actions on the central nervous system, so the authors speculated that the actions might be related to inhibition of the laryngeal reflex. 32,33) Zingiberis Rhizoma, an ingredient of Hange-koboku-to, contains 6-gingerol and 6-shogaol as its main bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%